The Influence of Symmetry on Children's Judgments of Facial Attractiveness. (March 2013) - Vingilis-Jaremko, Larissa; Maurer, Daphne
In experiment 1, we examined developmental changes in the influence of symmetry on judgments of attractiveness by showing adults and children pairs of individual faces in which one face was transformed 75% toward perfect symmetry, while the other face was transformed by exaggerating its asymmetries by 75%. Adults and 9-year-olds, but not 5-year-olds, rated the more symmetric faces as more attractive than the less symmetric faces, although the effect was stronger in adults than 9-year-olds. The preference for symmetry was stronger for male than female faces, and stronger for adults' than children's faces. In experiment 2, comparisons of the symmetry of the original male and female faces revealed no measured differences but lower ratings by adults of symmetry in the male faces. Overall, the results suggest that the influence of symmetry on attractiveness judgments emerges after the age of 5 years, and matures after the age of 9 years. The stronger effects for adult viewers may reflect an increase in sensitivity to symmetry as experience with faces increases and/or as the visual system matures. As well, attractiveness may become more salient after puberty, so that honest signals of mate quality, such as symmetry, have a stronger effect for adult viewers, especially when judging adult faces.